Archiving System for EAST PF Power Supply. (19th May 2022) - Wang, Guanghong; He, Shiying; Gao, Ge; Fu, Peng; Wang, Zejing; Chen, Xiaojiao; Zhang, Xiuqing; Zuo, Ying; Li, Lingpeng; Huang, Liansheng
Abstract: The poloidal field (PF) power supply is an important subsystem of the Experimental Advanced Superconducting Tokamak (EAST). The monitor system of the PF power supply is based on the Experimental Physics and Industrial Control System (EPICS), using Control System Studio (CSS) as the human-machine interface. Archive, which is for data archiving, is a plugin of CSS. This paper creates an archiving system, including archive engine, client, and relational database (RDB). The process variables that need to be archived are configured so that they can be stored to RDB when changed. Real-time archiving for all input signals is realized, and history data can be browsed at any time through CSS. The archiving system provides a data basis for analyzing the EAST PF power supply, applied to the EAST experiment for more than 5 years, showing stable performance.